1990
DOI: 10.1007/bf01913643
|View full text |Cite
|
Sign up to set email alerts
|

Thermoanalytical characterization of Aleksinac (Yugoslavia) oil shale kerogen

Abstract: The chemical nature of the kerogen from Aleksinac (Yugoslavia) oil shale was studied by thermal analysis of a kerogen concentrate and the partially degraded kerogen concentrates obtained as intermediates in ~ts stepwise alkaline permanganate oxidation. The initial kerogen concentrate decomposed in the range 200-550Oc and the DTG profile consisted of several overlapping peaks. The partially degraded kerogen concentrates were thermally more stable. Their thermograms consisted of two distinct parts: the low-(150-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Non-isothermal kinetic study of weight loss under the combustion process is extremely complex for a mixture of OS and semicoke because of the presence of numerous complicated components and parallel and consecutive reactions taking place [12][13][14][15]. In this research, binary linear regression method based on Arrhenius kinetic theory was used for kinetic analysis of the data obtained in the TG/DTG experiments.…”
Section: Combustion Reaction Kineticsmentioning
confidence: 99%
“…Non-isothermal kinetic study of weight loss under the combustion process is extremely complex for a mixture of OS and semicoke because of the presence of numerous complicated components and parallel and consecutive reactions taking place [12][13][14][15]. In this research, binary linear regression method based on Arrhenius kinetic theory was used for kinetic analysis of the data obtained in the TG/DTG experiments.…”
Section: Combustion Reaction Kineticsmentioning
confidence: 99%
“…Thermal characteristics and kinetic parameters of OS combustion have been extensively studied by isothermal and non-isothermal thermogravimetry [6][7][8][9][10], but few studies of semicoke combustion have been reported. Võssotskaja and Urov [11] developed an aluminium retort heated electrically to study the effect of kaolinite on thermal decomposition of kukersite oil shale using model mixtures.…”
Section: Introductionmentioning
confidence: 99%